Flipped learning in ESL classrooms - Mohammad Musab, Azmat Ali; Melor, Md Yunus; Harwati, Hashim; Siti Fatimah, Abd Rahman
The 21st century brings about unprecedented changes to society and how the education process takes effect in schools. the implementation of digital technology brings about a plethora of strategies and approaches to teaching with the aid of technology. The flipped learning approach is one of these approaches gaining momentum in the education scenario. Due to its students and learning centric nature of execution.